Atomistic Mechanics of Torn Back Folded Edges of Triangular Voids in Monolayer WS2. Issue 52 (27th October 2021) - Ryu, Gyeong Hee; Jung, Gang Seob; Park, Hyoju; Chang, Ren‐Jie; Warner, Jamie H.
Abstract: Triangular nanovoids in 2D materials transition metal dichalcogenides have vertex points that cause stress concentration and lead to sharp crack propagation and failure. Here, the atomistic mechanics of back folding around triangular nanovoids in monolayer WS2 sheets is examined. Combining atomic‐resolution images from annular dark‐field scanning transmission electron microscopy with reactive molecular modelling, it is revealed that the folding edge formation has statistical preferences under geometric conditions based on the orientation mismatch. It is further investigated how loading directions and strong interlayer friction, interplay with WS2 lattice's crack preference, govern the deformation and fracture pattern around folding edges. These results provide fundamental insights into the combination of fracture and folding in flexible monolayer crystals and the resultant Moiré lattices. Abstract : Combining atomic‐resolution images from annular dark‐field scanning transmission electron microscopy with reactive molecular modelling, it is revealed that the folding edge formation has statistical preferences under geometric conditions based on the orientation mismatch. It is further investigated how loading directions and strong interlayer friction, interplay with WS2 lattice's crack preference, govern the deformation and fracture pattern around folding edges.